KORELASI DAKWAH BIL-HAL DENGAN PENINGKATAN IBADAH AMALIYAH - zainudin zainudin (UIN Antasari Banjarmasin, 2018)
The concept of da'wah, especially da'wah bil-hal is basically one of the effective methods for conveying and preaching Islam to mankind, but the reality is as if a question arises whether or not there is a relationship between da'wah bil-hal and an increase in amaliyah worship. So that such problems provide their own views, to find gaps between preaching and worship. This type of research is quantitative research, which is a population of 400 Bangka students in Palembang, taken as many as 40 students (10%), with a porposive sample technique. The correlation coefficient of da'wah bil-hal with an increase in amaliyah worship is 0.182, at a significance level of 5% (r-table = 0.320). There is a relationship between the two variables, but the relationship level is weak. The causative factor is that many of the two variables are invalid and of the many respondents in this study are not pure students from Islamic universities